Portrait of Charles C. Price (1913-2001) - Apeda Studio (New York, N.Y.) (1960)
Black and white portrait of American chemist and American Chemical Society president (1965) Charles C. Price (1913-2001). An instructor at the University of Illinois at Chicago, the University of Notre Dame, and the University of Pennsylvania, Price is best known as a pioneer of polymer science and inventor of polyether polyurethane foam rubber, which became widely used in sponges, insulating building materials, flotation devices, and packaging.
Keywords: Price, Charles C. (Charles Coale), 1913-2001; Portraits; Chemists; Scientists with disabilities; People with disabilities; Polymers; American Chemical Society